Design and Development of a Virtual Reality-Based Mobility Training Game for People With Parkinson's Disease - Finley, James M.; Gotsis, Marientina; Lympouridis, Vangelis; Jain, Shreya; Kim, Aram; Fisher, Beth E. (Frontiers in Neurology, 2021)
People with Parkinson's disease (PD) commonly have gait impairments that reduce their ability to walk safely in the community. These impairments are characterized, in part, by a compromised ability to turn and negotiate both predictable and unpredictable environments. Here, we describe the development and usability assessment of a virtual reality training application, Wordplay VR, that allows people with PD to practice skills such as turning, obstacle avoidance, and problem-solving during over-ground walking in a game-based setting. Nine people with PD completed three sessions with Wordplay VR, and each session was directed by their personal physical therapist. Our outcome measures included perceived sense of presence measured using the International Test Commission - Sense of Presence Inventory (ITC-SOPI), levels of motivation using the Intrinsic Motivation Inventory (IMI), overall system usability using the System Usability Scale (SUS), and setup time by the physical therapists. Both the people with PD and the physical therapists rated their sense of presence in the training system positively. The system received high ratings on the interest and value subscales of the IMI, and the system was also rated highly on usability, both from the perspective of the patient during gameplay and the therapist while controlling the experience. These results suggest that the application and task design yielded an experience that was motivating and user-friendly for both groups. Lastly, with repeated practice over multiple sessions, therapists were able to reduce the time required to help their patients don the headset and sensors and begin the training experience.